COMPOSITION AND GRAPHIC TOOLS FOR THE DESIGN OF MEN'S CASUAL CLOTHES AND SPORTSWEAR - Чупріна, Н. В.; Струмінська, Т. В.; Пашкевич, К. Л.; Кокоріна, Г. В.; Давиденко, І. В.; Гаркін, П. В. (Art and Design, 2023)
The purpose of the research is to determine directions for designing men's clothing with improved functional properties, with the introduction of compositional and graphic means of street art; to characterize the collaboration of fashion design brands with the graphic works of street artists as a trend of developing a current project image in men's mass fashion. Methodology. The research methodology is based on the study of the principles of collaboration of various spheres of modern art and culture in the creation of a widely demanded design product. The research was carried out by studying, comparing, summarizing the preferences of the modern consumer in various areas of modern culture and certain subcultures (graffiti art, hip-hop music, promoting sports and an active lifestyle, etc.). The techniques of the analytical and typological methods are used, based on documentary sources (including photo and video), graphic works, fashion illustrations, analysis of event and performance presentations of fashion clothing collections as a product of fashion. An associative approach and a method of adapting visual characteristics in various spheres of the cultural phenomenon are used to describe the visual design solutions of the "hip-hop" stylistic direction in fashion. Results. The main trends of modern pop culture influencing the formation of current trends in street fashion, in particular in the development of men's clothing models, have been determined. The activity of street artists is characterized in the context of their influence on the development of modern art and the formation of the subject environment. A comparative description of the creative features of leading street art artists is given and an analysis of their interaction with leading designer brands in the creation and presentation of fashion clothing collections is presented. Their cooperation in the implementation of advertising campaigns of leading fashion brands, especially in the segment of street fashion, is characterized. The main stylistic features of the clothing of the hip-hop subculture of the 2010s, assimilated into the current street fashion trends of the 2020s, have been determined. The main directions of collaboration of representatives of the hip-hop subculture (music and sports) with leading fashion brands in the design of men's casual and sportswear, with the use of compositional and graphic means of street art decoration, have been determined. The project image of the consumer and models of men's clothing for everyday and sports purposes has been developed. Scientific novelty. The scientific novelty of the results is determined by the comprehensive justification of the development of a relevant fashion image (using the example of men's everyday clothes), which is based on the assimilation of modern art trends (graffiti), modern mass culture phenomena (hip-hop subculture) and design activities in the field of the fashion industry. The project-advertising strategy of the formation of fashionable clothes as a relevant design product based on the collaboration of representatives of various directions of the culture of the modern consumer society is characterized. The practical significance of the work is that it is filled with established reliable information of an interdisciplinary nature, which demonstrates a single comprehensive basis for the formation of the design image of the modern consumer and the creation of a design product of current men's clothing for everyday and sports purposes. The results of the research can be adapted and expanded when creating clothing models for different purposes, for different consumer segments for promotion in the modern fashion clothing market.